2015
DOI: 10.5657/fas.2015.0065
|View full text |Cite
|
Sign up to set email alerts
|

Expression Patterns of the chgH:rfp Transgene in Response to 17α-Ethinylestradiol (EE2) Exposure in Marine Medaka Oryzias dancena

Abstract: The functional utility of a transgenic marine medaka Oryzias dancena strain carrying the red fluorescent protein (RFP) gene driven by an endogenous choriogenin H (chgH) promoter was evaluated for its ability to detect waterborne 17α-ethinylestradiol (EE2), a synthetic estrogen derivative. The chgH:rfp transgenic marine medaka larvae showed an age-dependent tendency in the efficiency of EE2-mediated transgene expression, in which transgenic larvae older than 6 days post-hatching displayed a more effective respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, in the present study, none of transgenic females showed naturally occurring RFP signals, suggesting that the regulation of transgenic chgH would not be robust yet in sexually differentiated, but immature, transgenic fish, which is generally in accordance with the anticipated role of the choriogenin as the main constitute of egg envelop (Hong et al 2009). However, these young immature individuals have been proven to respond readily to exogenously administered estrogens as reported previously (Cho et al 2013;Nam et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the present study, none of transgenic females showed naturally occurring RFP signals, suggesting that the regulation of transgenic chgH would not be robust yet in sexually differentiated, but immature, transgenic fish, which is generally in accordance with the anticipated role of the choriogenin as the main constitute of egg envelop (Hong et al 2009). However, these young immature individuals have been proven to respond readily to exogenously administered estrogens as reported previously (Cho et al 2013;Nam et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Of various estrogen-responsive transgenic lines generated in marine medaka, the transgenic strain used in this study was the stable line showing the strongest and the most sensitive response to both natural and synthetic versions of the estrogen compounds. Characteristics of this transgenic line [labeled TG#038 in Cho et al (2013)] in details could be referred to our previous reports (Cho et al 2013;Nam et al 2015).…”
Section: Transgenic Fish Strainmentioning
confidence: 99%
See 2 more Smart Citations